2021
DOI: 10.1021/acs.orglett.1c00929
|View full text |Cite
|
Sign up to set email alerts
|

Water-Mediated Catalytic Decarboxylation Enabled Polysubstituted Furans and Allylic Alcohols with Exclusive (E)-Configurations

Abstract: A water-mediated catalytic decarboxylation process toward the formation of polysubstituted furans and (E)-allylic alcohols has been reported. This protocol features wide functional group tolerance, easy operation, and only CO 2 -byproduct generation. These reactions can be performed on a large scale open to air under extremely ambient conditions. A range of control experiments revealed the crucial role of the water for the successful conversions as well as the origin of the chemoselectivity and exclusive stere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 43 publications
2
12
0
Order By: Relevance
“…By using water as a nucleophile, functionalized furans can be obtained (Scheme 4a , path b). 19 ( E )-γ-hydroxy ketones can be prepared simply by changing the palladium-based catalytic system (Scheme 4a , path c). By prolonging the reaction time, these ( E )-γ-hydroxy ketones can be transformed into furans via Pd–allyl intermediates in which the floppy hydroxy group acts as a leaving group, with water as the nucleophile.…”
Section: Nucleophilic Capture Of Zwitterionic Metal (Palladium or Cop...mentioning
confidence: 99%
See 1 more Smart Citation
“…By using water as a nucleophile, functionalized furans can be obtained (Scheme 4a , path b). 19 ( E )-γ-hydroxy ketones can be prepared simply by changing the palladium-based catalytic system (Scheme 4a , path c). By prolonging the reaction time, these ( E )-γ-hydroxy ketones can be transformed into furans via Pd–allyl intermediates in which the floppy hydroxy group acts as a leaving group, with water as the nucleophile.…”
Section: Nucleophilic Capture Of Zwitterionic Metal (Palladium or Cop...mentioning
confidence: 99%
“…13 Our group recently designed a batch of different functionalized methene carbonates A, B, and C, the decarboxylation of which under transition-metal catalyst generates the corresponding zwitterionic metal enolate (ZME) intermediates T1-3 or their equivalents (Scheme 2). [14][15][16][17][18][19][20] We have proved that these ZME intermediates can be captured by various reaction partners to afford various, optionally enantioenriched, functionalized ketones or their derivatives, some of which are otherwise synthetically quite challenging. More specifically, with regard to the ZME intermediates, the enolate portion not only works as a precursor of a carbonyl functionality, but also acts as hydrogen-bonding acceptor that might assist in the introduction of high enantioselec-tivity or regioselectivity; the metal-containing cation fragment permits a wide choice of versatile catalytic systems.…”
Section: Introductionmentioning
confidence: 99%
“…It was previously demonstrated that the nucleophilic attack of water on the Pd-allyl intermediate derived from the decarboxylation of VCCs could lead to a series of polysubstituted allyl alcohols with exclusive Z -configuration (Scheme 19a ). 29 In contrast, this method 28 could be used to prepare polysubstituted E -allyl alcohols. This protocol also displays broad substrate scope and good functional group tolerance.…”
Section: Zwitterionic Enolate Chemistry Based On Transition-metal Cat...mentioning
confidence: 99%
“…Interestingly, the attack of nucleophilic water on the zwitterionic enolate intermediate proved to be feasible, resulting in either functionalized furans or α,β-unsaturated ketones. 28 The chemoselectivity could be well controlled under different reaction conditions (see Scheme 19b ). It was previously demonstrated that the nucleophilic attack of water on the Pd-allyl intermediate derived from the decarboxylation of VCCs could lead to a series of polysubstituted allyl alcohols with exclusive Z -configuration (Scheme 19a ).…”
Section: Zwitterionic Enolate Chemistry Based On Transition-metal Cat...mentioning
confidence: 99%
“…In this context, some new variants of VECs have been reported. Most recently, the Zi group and the Guo group designed vinyl methylene cyclic carbonates (VMCCs) to act as reactive precursors to Pd-oxyallyl species independently for annulation reactions and developed [3+2] and [5+2] annulations of VMCCs with electron-deficient alkenes. Encouraged by our interest in the development of new Pd-catalyzed annulation reactions, we considered the design of novel cyclic carbonates from different perspectives.…”
mentioning
confidence: 99%